Serratia liquefaciens Infection of a Previously Excluded Popliteal Artery Aneurysm - A. Coelho; M. Lobo; V. Martins; R. Gouveia; P. Sousa; J. Campos; R. Augusto; N. Coelho; A. Canedo (EJVES Short Reports, 2017)
: Introduction: Popliteal artery aneurysms (PAAs) are rare in the general population, but they account for nearly 70% of peripheral arterial aneurysms. There are several possible surgical approaches including exclusion of the aneurysm and bypass grafting, or endoaneurysmorrhaphy and interposition of a prosthetic conduit. The outcomes following the first approach are favorable, but persistent blood flow in the aneurysm sac has been documented in up to one third of patients in the early post-operative setting. Complications from incompletely excluded aneurysms include aneurysm enlargement, local compression symptoms, and sac rupture. Notably infection of a previously excluded and bypassed PAA is rare. This is the third reported case of PAA infection after exclusion and bypass grafting and the first due to Serratia liquefaciens. Methods: Relevant medical data were collected from the hospital database. Results: This case report describes a 54 year old male patient, diagnosed with acute limb ischaemia due to a thrombosed PAA, submitted to emergency surgery with exclusion and venous bypass. A below the knee amputation was necessary 3 months later. Patient follow-up was lost until 7 years following surgical repair, when he was diagnosed with aneurysm sac infection with skin fistulisation. He had recently been diagnosed with alcoholic hepatic cirrhosis Child–Pugh Class B. The patient was successfully treated by aneurysm resection, soft tissue debridement and systemic antibiotics. Conclusion: PAA infection is a rare complication after exclusion and bypass procedures but should be considered in any patient with evidence of local or systemic infection. When a PAA infection is diagnosed, aneurysmectomy, local debridement, and intravenous antibiotic therapy are recommended. The “gold standard” method of PAA repair remains controversial. PAA excision or endoaneurysmorrhaphy avoids complications from incompletely excluded aneurysms, but is associated with a high risk of neurological damage. Keywords: Popliteal artery, Aneurismatic disease, Infection, Hepatic cirrhosis, Popliteal aneurysm exclusion